Stability Analysis for Mutually Delay-Coupled Semiconductor Lasers System - Rina Su; Chunrui Zhang; Zuolin Shen (Abstract and Applied Analysis)
In this paper, the problem of the stability for mutually delay-coupled semiconductor lasers system is investigated. By analyzing the associated characteristic equation, linear stability is investigated and Hopf bifurcations are demonstrated. The new phenomena such as stability switch is found. The Z2 equivariant property and the existence of multiple periodic solutions is also discussed. Numerical simulations are presented to illustrate the results in the paper.